Identifying, Understanding, and Handling Bad, Ineffective, and Toxic Leaders and Followers - Grunberg, Neil E.; McManigle, John E.; Barry, Erin S. (Journal of Leadership, Accountability and Ethics, 2021)
Leadership development has long been a focus within businesses, governments and the military. During the past several decades, leadership development has expanded to all levels of schooling and personal growth. Many articles, books, blogs, and podcasts address poor leadership and followership and the associated characteristics and consequences. Yet, there currently is not a standard lexicon to describe and differentiate among the various types. The present paper offers a framework that can be applied to understand issues that contribute to poor leadership and followership, considering, Character, Competence, Context, Communication (Four C Elements). Additionally, poor leaders and followers can be categorized into three different groups – Bad, Ineffective, Toxic (BIT). Identifying the relevant BIT category and Four C Elements is the first step to address difficult individuals and situations. The next step is determining how to deal with these BIT leaders or followers. These specific classifications will help leaders and followers find the best way to handle BIT leaders and followers.